Counter-immunoelectro-osmophoresis for the detection of infantile gastroenteritis virus (orbi-group) antigen and antibody. Issue 3 (March 1976) - Middleton, P J; Petric, M; Hewitt, C M; Szymanski, M T; Tam, J S
Abstract : A moderatley sensitive, rapid, and economical test scheme for the detection of infantile gastroenteritis virus (IGV) in stool or antibody in serum has been developed and evaluated. The test scheme with minor modifications was an adaptation of a counter-immunoelectro-osmophoresis system we once used for the detection of hepatitis B antigen. Large numbers of stool samples may be screened during half a working day for the presence of IGV using reference antiserum to IGV prepared in guinea-pigs. Serological studies of a diagnostic but not epidemiological nature may also be performed with equal facility by this same test scheme using highly purified IGV antigen derived from stool.